A Simple Method to Differentiate between Free-Carrier Recombination and Trapping Centers in the Bandgap of the p-Type Semiconductor - Megersa Wodajo Shura (Advances in Materials Science and Engineering)
In this research, the ranges of the localized states in which the recombination and the trapping rates of free carriers dominate the entire transition rates of free carriers in the bandgap of the p-type semiconductor are described. Applying the Shockley–Read–Hall model to a p-type material under a low injection level, the expressions for the recombination rates, the trapping rates, and the excess carrier lifetimes (recombination and trapping) were described as functions of the localized state energies. Next, the very important quantities called the excess carriers’ trapping ratios were described as functions of the localized state energies. Variations of the magnitudes of the excess carriers’ trapping ratios with the localized state energies enable us to categorize the localized states in the bandgap as the recombination, the trapping, the acceptor, and the donor levels. Effects of the majority and the minority carriers’ trapping on the excess carrier lifetimes are also evaluated at different localized energy levels. The obtained results reveal that only excess minority trapping affects the excess carrier lifetimes, and excess majority carrier trapping has no effect.